2018
DOI: 10.1177/1071100718786498
|View full text |Cite
|
Sign up to set email alerts
|

Results of Scarf Osteotomy Without Implant Fixation in the Treatment of Hallux Valgus

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, it must be taken into account that HV surgery with ReveL osteotomy, with a long plantar limb, has inherently high primary stability due to the surgical technique. In the past, some studies have even reported that there was no significant slippage of the osteotomy even without additional screw stabilization [ 20 , 21 ]. In some centers, only a K-wire is used as an alternative to the 3.0 mm head compression screw (HCS), which is routinely used in our clinic [ 2 , 3 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be taken into account that HV surgery with ReveL osteotomy, with a long plantar limb, has inherently high primary stability due to the surgical technique. In the past, some studies have even reported that there was no significant slippage of the osteotomy even without additional screw stabilization [ 20 , 21 ]. In some centers, only a K-wire is used as an alternative to the 3.0 mm head compression screw (HCS), which is routinely used in our clinic [ 2 , 3 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scarf is a 3-plane osteotomy that also enables correction of the first ray in the sagittal plane (plantarization or elevation). 4,5 As Meary's angle is determined by longitudinal axes of the first metatarsal and talus on lateral weightbearing foot radiographs, scarf osteotomy may have an influence on postoperative T1MA. We regret that the authors did not measure postoperative T1MA or correlate values with hallux valgus recurrence rates.…”
Section: Dear Editormentioning
confidence: 99%
“…Several modifications of the scarf osteotomy have been described in the literature. 1,2,4,5 These modifications are dependent on the surgeon and influence the final outcome in the sagittal plane and T1MA (Figure 1 and Figure 2).…”
mentioning
confidence: 99%
“…The orientation of the incisions influences plantarisa-tion (plantary directed cuts), shortening (proximally directed cuts), or rotation/derotation (turning distal fragment medially or laterally with different amounts of translation in the proximal and distal parts of the osteotomy) (Figure 1b-e) 7,8 . Adequate tailoring and interpressing bone fragments allow the surgeon to achieve maximum primary stability of the osteotomy even without the need for screw fixation (Figure 2) 9,10,11 . Scarf osteotomy is indicated for medium and large deformities of the hallux valgus, with an expected reduction of the intermetatarsal angle (IMA) and the hallux valgus angle (HVA).…”
Section: Introductionmentioning
confidence: 99%